Penguatan Prinsip-Prinsip Negara Hukum Pancasila melalui Administrasi Pemerintahan Daerah di Indonesia - Sugirman, Andi (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2024)
This study aims to analyze the role of local government administration in strengthening and implementing the principles of the Pancasila Law State in Indonesia. The Pancasila Law State, as the ideological and legal foundation of Indonesia, requires all government activities to be based on law and Pancasila values. Through a normative juridical approach, this research examines how local governments, through their policies and actions, can play a key role in realizing the ideals of the Pancasila Law State. The findings indicate that despite a supportive legal framework, there are significant challenges in its implementation, including issues of corruption, nepotism, and bureaucratic inefficiency. Therefore, it is necessary to strengthen the capacity and integrity of local government officials and increase public participation to ensure the effective implementation of Pancasila principles. This study recommends strategic steps to enhance the role of local governments in this context, including improving transparency, accountability, and inter-agency coordination.